(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article covers the main objectives of the activities of agents in the field of sports. At the same time, there are obligations that can be included in the agency agreement based on the rules of civil law in this area. The main objectives of the activities of agents in the field of sports are to identify the most relevant.